2017
DOI: 10.4236/ojepi.2017.73018
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Factors Influencing Medication Adherence to Hypertension Treatment in Developing Countries

Abstract: Background: Coronary heart disease (CHD), a complication of hypertension, is one of the most important and common causes of morbidity, hospitalisation, and mortality among hypertensive population. In recent decades, increased urbanisation and changes to lifestyle, diet and physical activity in developing countries have led to a major increase in the population incidence of chronic diseases including CHD. Poor medication adherence is one of the leading causes of failure to achieve hypertension control. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 50 publications
(62 reference statements)
4
42
0
4
Order By: Relevance
“…20,21,24,25,30 Even if a weak health system is one of the major obstacles to tackle hypertension in developing countries, little attention has been given to assess the role of local health systems in the delivery of care for the control of hypertension. 13 Factors associated with antihypertensive medication adherence reported in studies included in this review were diverse and described in different ways across the studies. Since only a limited number of studies reporting comparable factors, it was not possible to make an MA for the main factors affecting adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21,24,25,30 Even if a weak health system is one of the major obstacles to tackle hypertension in developing countries, little attention has been given to assess the role of local health systems in the delivery of care for the control of hypertension. 13 Factors associated with antihypertensive medication adherence reported in studies included in this review were diverse and described in different ways across the studies. Since only a limited number of studies reporting comparable factors, it was not possible to make an MA for the main factors affecting adherence.…”
Section: Discussionmentioning
confidence: 99%
“… 12 In developing countries, the prevalence of medication non-adherence among the hypertensive population ranged from 23% to 67.6% with the mean being 47.34%. 13 …”
Section: Introductionmentioning
confidence: 99%
“…[35] A systematic review evaluating medication adherence factors for hypertension in developing countries cited other factors such as cost barriers, irregular follow-ups, and competing availability of traditional herbal remedies. [36] When it comes to the treatment of hypertension, a key challenge especially among the less educated is the reconciliation of the disease's asymptomatic nature and its downstream life-threatening complications. Moreover, the undertaking of educating about the importance of hypertension control in the Southeast Asian context is further complicated by differing pathogenetic models in the fields of traditional, complementary, and alternative medicine pervasive in the region.…”
Section: Factors Resulting In Poor Hypertension Controlmentioning
confidence: 99%
“…Suggestion by unqualified doctors (village doctors) in Bangladesh is also an important cause of stopping taking drugs. 29 Use of herbal medicine is also an important cause of nonadherence among the patients in developing countries, 18 though we haven't studied the use of herbal medicine in our patient population.…”
Section: Methods-mentioning
confidence: 99%
“…In a systemic review involving the studies in developing countries, it was concluded that low household income and socioeconomic status; knowledge and beliefs of hypertension and its management; avoiding side effects of medications; cost of medication; use of herbal preparations; absence of symptoms; irregular follow-up; and dissatisfaction with the treatment and health services provided. 18 A study of the Prevalence, Awareness, Treatment and Control of Hypertension among Elderly in Bangladesh and India found that 45% of elderly people in these two countries suffer from hypertension, 40% of the patients are aware of their disease diagnosis and 10% of them are adhering to treatment. 19 A number of studies were conducted in different regions of Bangladesh in different institutions and field levels.…”
mentioning
confidence: 99%